A Feasibility Study Of Chlorination Of Wells By Peripheral Workers - Gaur D.R; Dahiya B.R; Sood A.K (Indian Journal of Community Medicine, 1989)
Chlorination of wells water by the use of bleaching power is one of the most simple and cheap methods of assuring safe potable water in rural areas. The multipurpose health workers are entrusted with this task. These health workers were interviewed with a semi-structured open-ended schedule and their working was observed by work-study to know the difficulties faced by them during the process of chlorination. Majority of the workers were of the opinion that daily chlorination of wells during an outbreak of gastroenteritis in their respective areas was not feasible within the resources available at the block level. The main difficulties faced by them were the large number of wells and inadequate equipment for chlorination. The work-study revealed that most of the workers did not follow the correct method of chlorination and this invariably resulted in super-chlorination of well water thereby decreasing its acceptability by the community. The involvement of local volunteers could be possible solution in rural areas.